2020
DOI: 10.1093/dote/doaa080
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Achalasia Quality of Life and Eckardt scores for assessment of clinical improvement post treatment for achalasia

Abstract: Achalasia Quality of Life (ASQ) and Eckardt scores are two patient-reported instruments widely used to assess symptom severity in achalasia patients. ASQ is validated and reliable. Although Eckardt is commonly used, it has not been rigorously assessed for validity or reliability. This study aims to evaluate (i) the accuracy of Eckardt and ASQ for assessing improvement post-treatment (predictive validity), (ii) accuracy of Eckardt and ASQ for assessing improvement post-treatment with pneumatic dilatation (PD) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 12 publications
4
27
1
1
Order By: Relevance
“…Very few studies have reported on correlation of ES with ASHRQoL and physiological parameters 4,23. In our study, a strong correlation was seen between ES and ASHRQoL ( r =0.41), similar to a recent study by Slone and colleagues with a correlation coefficient of 0.85 (95% confidence interval: 0.75-0.91).…”
Section: Discussionsupporting
confidence: 90%
“…Very few studies have reported on correlation of ES with ASHRQoL and physiological parameters 4,23. In our study, a strong correlation was seen between ES and ASHRQoL ( r =0.41), similar to a recent study by Slone and colleagues with a correlation coefficient of 0.85 (95% confidence interval: 0.75-0.91).…”
Section: Discussionsupporting
confidence: 90%
“…Symptom improvement was based on post‐treatment clinic visits recorded in the chart by the senior author using a modified Eckardt scale or a telephone survey comparing the Eckardt scale 10 and the Achalasia Quality of Life scale 11 . Improvement was defined by an Eckardt scale of <4 12 …”
Section: Methodsmentioning
confidence: 99%
“…The median pre-BSP Eckardt score was 9 (6-12), and decreased to 4 (2-6) after 1 month (P = 0.001), and maintained up to 9 years (2 [1][2][3]; P = 0.14). Dakkak score didnʼt show changes between pre-BSP and post-BSP 1-month and 2-month values; however, they improved at 3 months (pre-BSP = 4 [2][3][4] vs post-BSP 3 months = 1 0-2; P = 0.001), and values were maintained up to 9 years (post-BSP 3 months = 1 0-2 vs post-BSP 9 years = 2 0-2; P = 0.09).…”
Section: Biodegradable Stent Placement (Early Mid- and Long-term Outcomes)mentioning
confidence: 95%
“…At 1 month, we had six migrations, requiring a second stent placement, fixed with a median of three hemoclips (2)(3)(4). At 2 months all stents were in place.…”
Section: Biodegradable Stent Placement (Early Outcomes)mentioning
confidence: 99%
See 1 more Smart Citation